1978
DOI: 10.1042/bj1730475
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the glycosphingolipids of chicken bursa of Fabricius and of chicken, rat and human thymus

Abstract: 1. The glycosphingolipid compositions of the thymus and bursa of Fabricius of young male chickens were compared. The two tissues were found to contain complex mixtures of both neutral glycosphingolipids and gangliosides. Both tissues contained mono-, di-, tri-, tetra- and penta-glycosylceramides; the pentaglycosylceramide displayed a reaction of identity with authentic Forssman antigen when tested against a specific anti-(Forssman antigen) serum. The ganglioside G(m3) containing N-acetylneuraminic acid was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The occurrence of galabiosylceramide has been documented for embryonic muscle [I 41. and thymus and bursa Fabricii of young chicken [16]. Thus, the ability to synthesize gala-series glycolipids seems to be charactistic for chicken tissues and can be traced back to very early developmental stages, as our results suggest.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The occurrence of galabiosylceramide has been documented for embryonic muscle [I 41. and thymus and bursa Fabricii of young chicken [16]. Thus, the ability to synthesize gala-series glycolipids seems to be charactistic for chicken tissues and can be traced back to very early developmental stages, as our results suggest.…”
Section: Discussionsupporting
confidence: 64%
“…Similar to other animal species, ganglioside Ggall in the chicken becomes a major constituent of brain myelin [23]. Ganglioside Gga11 was also found to be present in chicken thymus [16].…”
Section: Discussionmentioning
confidence: 62%
“…6 C). As rat lymphocytes have significant amounts of GMI (24) and toxin receptors (~40,000 per cell from Fig. 6A), the small effect on toxin action by exogenous GM 1 was not unexpected.…”
Section: Evidence For Functional Insertion Of Exogenous Gangliosides mentioning
confidence: 82%
“…Using a monoclonal antibody specific to GM4, Ozawa et al reported that the expression of GM4 in chicken cerebellum was associated with astrocytes, and not with myelin (6). The occurrence of GM4 in extraneural tissues was first reported in chicken egg yolk (7) and chicken thymus (8). This ganglioside has also been detected in mouse erythrocytes (9,10), rat kidney (11), chicken embryonic liver (12), chicken liver (13), and frog liver (14).…”
mentioning
confidence: 99%